STRATEGI SUPARTO BRATA DALAM KONTESTASI SIMBOLIK DI ARENA SASTRA INDONESIA PADA MASA ORDE BARU (TAHUN 1990-AN) - , Dheny Jatmiko, Dr. Aprinus Salam, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is entitled Suparto Brataâs Strategy in Symbolic Contestation in Field of Indonesian Literary during The New Order (1990s). The background of this research is the failure Suparto Brata in the symbolic contestation in field of Indonesian literary during the New Order by novel Mencari Sarang Angin. Suparto Brata is a writer who has written many literary works whether it is in Indonesian or Javanese language and acheved SEA Award 2007. However, his productivity didnât gain any achievment nor legitimation as a writer during the New Order. This research scientifically aims to apply Pierre Bourdieu's genetic structuralism theory in analyzing the field of cultural production of novel Mencari Sarang Angin. The practical objective of this research is to obtain an illustration abaout the field of cultural production of novel Mencari Sarang Angin, therefore the reason of his failure in symbolic contestation can be explained. It is found that during the New Order, field of Indonesian literary was dominated by universal literature. The available vacancies for literary works were universal literature, contextual literature, popular literature, and ethnic literature. In the New Order, field of Indonesian literary has its own rule in order to maintain the dominating power, which is by distancing themselves from politics and the economics, and has to be national widespread. In the the trajectory analysis, it is found that the Suparto Brataâs habitus is an educated aristocracy that internalized two different subcultures of Javanese culture, and middle class society that dominated by the dominant class. He focused on the contestation in field of Indonesian literary during the New Order through his works, one of them is Mencari Sarang Angin. Suparto Brata has the capital to be distributed: economic capital (wealth), cultural capital (culture, data, writing skills, historical and cultural knowledge about Surabaya, and ability to write novel in detective formula), social capital (networking in field of Javanese and Surabaya literature), and symbolic capital (the legitimation as Javanese writer and other achievment) . With his strategies, Suparto Brata distributed those capital to struggle and fight off in field of Indonesian literature, in order to gain revenues, whether it is symbolic and economic revenues. Suparto Brataâs strategies cover textual strategies: the characterâs neutral attitude between domination-dominated and taking side 'between' serious and popular literature